2015
DOI: 10.1007/978-1-4939-2425-7_29
|View full text |Cite
|
Sign up to set email alerts
|

MAPPIT, a Mammalian Two-Hybrid Method for In-Cell Detection of Protein-Protein Interactions

Abstract: MAPPIT (MAmmalian Protein-Protein Interaction Trap) is a two-hybrid technology that facilitates the detection and analysis of interactions between proteins in living mammalian cells. The system is based on type 1 cytokine receptor signaling. The bait protein of interest is fused to a chimeric signaling-deficient cytokine receptor, the signaling competence of which is restored upon recruitment of a prey protein that is coupled to a functional cytokine receptor domain. MAPPIT exhibits an excellent signal-to-nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Finally, we retested 93 randomly selected protein pairs using the MAmmalian Protein-Protein Interaction Trap (MAPPIT), which detects interactions between proteins in living cells based on restoration of the signaling capacity of a signaling-deficient cytokine receptor 16 , 17 ( Supplementary Table 4 ). We examined the fraction that tested positively at a range of assay stringency thresholds, and compared the results with three previously published C. elegans MAPPIT analyses 18 : a positive reference set of 46 low-throughput literature-curated interactions ( Ce PRS), a set of 86 random protein pairs that serves as a negative control ( Ce RRS), and a set of 87 interactions detected in a large scale Y2H screen (WI-2007) 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we retested 93 randomly selected protein pairs using the MAmmalian Protein-Protein Interaction Trap (MAPPIT), which detects interactions between proteins in living cells based on restoration of the signaling capacity of a signaling-deficient cytokine receptor 16 , 17 ( Supplementary Table 4 ). We examined the fraction that tested positively at a range of assay stringency thresholds, and compared the results with three previously published C. elegans MAPPIT analyses 18 : a positive reference set of 46 low-throughput literature-curated interactions ( Ce PRS), a set of 86 random protein pairs that serves as a negative control ( Ce RRS), and a set of 87 interactions detected in a large scale Y2H screen (WI-2007) 18 .…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that cell-specific regulatory proteins binding to and shaping TRPV4 function could play a role in the pathophysiology of TRPV4-pathies. In order to discover proteins interacting with human TRPV4, we performed a MAPPIT screening [15]. MAPPIT is a two-hybrid technology based on the functional complementation of a human type 1 cytokine receptor.…”
Section: Identification Of Zc4h2 As a Novel Trpv4 Interactormentioning
confidence: 99%
“…It has been suggested that the divergent pathological effects of the disease-causing TRPV4 mutations in various tissues may involve altered interaction with cell-specific regulatory proteins [6]. In this study, we made use of the mammalian protein-protein interaction trap (MAPPIT) [15] to search for proteins that interact with the cytosolic N-terminus of TRPV4. We identified the zinc-finger C4H2-type containing protein (ZC4H2) as a TRPV4 interaction partner, and provide evidence that it augments TRPV4-mediated Ca 2+ signals and enhances channel turnover at the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies illustrate that targeting the interaction between E2 and other identified host cellular proteins could be an efficient therapeutic strategy to eliminate persistent infection [ 47 , 48 , 64 , 65 , 66 ], providing a framework with which to approach developing HPV-specific therapeutics. Highly specific visualization/detection techniques such as bimolecular fluorescence complementation and Mammalian Protein–Protein Interaction Trap (MAPPIT) will likewise prove integral to identifying these synthetic and naturally occurring small molecule inhibitors [ 57 , 90 , 91 , 92 ].…”
Section: Current Therapeutic Strategies For Clearing Persistent Hpmentioning
confidence: 99%